The Risk of Enamel Demineralization Around Braces and Prevention Strategies - Axtamovich, Rajabov Amirjon (Journal of Science in Medicine and Life, 2025)
Relevance.However, thesedrugs do notalwaysgive the desiredeffect,as65-67% of the examinedpatientshavepoororalhygiene,andlocalfluoridation is not effectiveenoughdue to therapidloss of calciumfluoridecrystals.For the preventionandtreatment of dentalhardtissuelesions, a method of deepfluoridationwith tiphenfluorides has beenproposed,whichreleasefluorideinhighconcentrationsfor a longtime,contributing to reliableremineralization.Currently, manyfundamentalaspects of preventionin the process of orthodontictreatmenthavenot yet been fullyresolved. There is nodataon the useofdeepfluoridationinorthodontics. The issues of assessing the resistance of toothenameland the effectiveness of remineralizingagentsusing the electrometricmethodin the process of orthodontictreatment have not been sufficientlyhighlighted. There are noeffectivemotivationalmethods for teachingandself-monitoring the quality of dentalcleaning for orthodonticpatients.In this regard, theurgenttaskis the furtherdevelopment of preventivemeasuresin the process of orthotictreatment.